An investigation of allergy in byssinosis: sensitization to cotton, hemp, flax and jute antigens. Issue 2 (April 1969) - Popa, V.; Gavrilescu, N.; Preda, N.; Teculescu, D.; Plecias, M.; Cîrstea, M.
Abstract : Popa, V., Gavrilescu, N., Preda, N., Teculescu, D., Plecias, M., and Cîrstea, M. (1969). Brit. J. industr. Med., 26, 101-108. An investigation of allergy in byssinosis: sensitization to cotton, hemp, flax, and jute antigens. The authors investigated allergy to cotton, hemp, flax, and jute in 41 subjects with byssinosis. In contrast with immediate skin reactions, which were seldom observed, delayed reactions were nearly always present. The incidence of positive skin tests in byssinosis was similar to that observed in all textile workers. Inhalation tests with textile allergens were negative in all but four subjects who also had a concomitant bronchial asthma. Fifteen out of 31 subjects with byssinosis had positive inhalation tests to acetylcholine but only one of the 13 tested had a positive response to the inhalation of textile macerate. Haemagglutinating antibodies to low titres could be observed in byssinosis as well as in chronic bronchitis, in bronchial asthma, and in the general population. The significance of various types of antibodies existing in byssinosis is further discussed. The authors stress the need to standardize textile allergens.